LoRa System with IOT Technology for Smart Agriculture System - Edwin L.; Lee H.J.; Ker P.J.; Jamaludin M.Z.; Akhmal Abu Bakar M.A.; Awang R.; Yusuf F.A.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Internet of things; Low power electronics; Rural areas; Signal to noise ratio; Transceivers; Wide area networks; Agriculture systems; Energy; Long distance; Long range systems; Low Power; Multiple nodes; RF modulation; Security; Smart agricultures; Wide-area networks; Agriculture